Establishing a core dossier for multiple regulatory submissions: a case study in the Latin America region - Alvarez, Alva Lucia; Maisonet, Irma O.; Ruiz, Omar; Lumsden, Rebecca S.; Ferreira, Ana Paula Evangelista; Avila Flores, Esther M. (Frontiers in Medicine, 2023)
The Latin America region comprises several countries that do not follow harmonized regulatory requirements for drug product (DP) marketing authorization applications (MAA), resulting in customized registration dossiers for each country. Here, we established a core dossier for multiple MAA in the Latin America region by examining the similarities between regulatory requirements and reconciling their potential discrepancies through discussions among all national regulatory representatives. The core dossier was used in the submission of a new small molecule, NME1, to nine markets. Assessment of the process included the time to submission; the timing, number, and complexity of questions received; and timing of final national regulatory agencies (NRA) evaluation decisions. The core dossier resulted in an accelerated submission timeline for most markets and earlier receipt of NRA queries from some markets, compared with projections. One round of queries of a low or medium complexity was received from all agencies. The receipt of final NRA evaluation decisions was also accelerated in most markets, compared with the best-case approval timeframes. The core dossier approach was also evaluated against the standard submission of a similar small molecule, NME2. In contrast to the core dossier submission of NME1, a second round of questions, and high-complexity questions were received from two markets for NME2. In conclusion, a core dossier has the potential to simplify the regulatory process for both reviewers and applicants in regions that do not share harmonized regulatory requirements, with a consequential acceleration of DP approvals.